KOMITMEN ANTIKORUPSI DALAM PIDATO PRESIDEN PRABOWO: ANALISIS WACANA KRITIS MODEL NORMAN FAIRCLOUGH - Ivan Solihudin; Yudha Surya Nugraha; Jeremias M.de Carvalho (Jurnal Common, 2026)
The practice of corruption in Indonesia remains highly resilient due to the deeply entrenched influence of the oligarchy within the bureaucracy. Consequently, the president utilizes political communication as a strategic instrument for policy intervention. This study aims to examine the anti-corruption discourse embedded in President Prabowo Subianto's speech delivered on December 24, 2025, with a particular focus on the coinage of the neologism "Serakahnomics." Adopting a qualitative approach, this research employs Norman Fairclough’s model of Critical Discourse Analysis (CDA) to analyze the textual data derived from the speech transcript. The results indicate three primary findings. First, at the textual level, the deployment of the term "Serakahnomics" concretely frames grand corruption as an existential threat capable of devastating the state. Second, in terms of discursive practice, the delivery of the speech is strategically designed to demonstrate the government's legal decisiveness while simultaneously mobilizing widespread public support. Third, within the broader sociocultural context, this discourse actively seeks to dismantle the dominance of corrupt corporate entities and foster a spirit of nationalism aimed at safeguarding state assets. This study concludes that the neologism coined in the presidential speech transcends mere rhetorical device; rather, it functions as a potent instrument of political communication intended to combat bureaucratic corruption and undermine oligarchic power. Keywords: Critical Discourse Analysis, Political Communication, Neologism, Oligarchy, Serakahnomics.